Beijing Consensus Or Washington Consensus : What Explains China's Economic Success? - Yao, Yang (2012)
China's remarkable economic growth is often attributed to strong government intervention that can mobilize large amounts of resources to clear any bottleneck to growth or institutional change. This approach is often referred to as the Beijing Consensus (BC) as compared to the Washington Consensus (WC): the former being a model of authoritarianism and heavy state involvement in the economy, the latter a model of neoliberal and market-oriented doctrines. But these characterizations are inaccurate.